Locations of Adelie penguins from geolocating dive recorders 2017-2019 - Ballard, Grant; Schmidt, Annie; Lescroel, Amelie; Dugger, Katie; Ainley, David; Lisovski, Simeon (U.S. Antarctic Program (USAP) Data Center, 2021)
Positions of migrating, molting, and wintering Adelie penguins from Cape Royds and Cape Crozier, Ross Island as calculated from geolocation sensors (GLS) using probabilistic methods (R package SGAT)